EFFECTS OF HUMAN FACTORS IN THE EXISTENCE OF BALI STARLING (Leucopsar rothschildi) THROUGH GEOGRAPHIC INFOMATION SYSTEM APPROACH IN WEST BALI NATIONAL PARK AND NUSA PENIDA BALI - Fadlan Pramatana; Jarwadi Budi Hernowo; Lilik Budi Prasetyo (Media Konservasi, 2021)
Bali starling (Leucopsar rothschildi) is one of the animals that getting more attention because is categorized as an endengered species on the IUCN red list, Appendix 1 of CITES, and protected animals by goverment of Indonesia. The conservation for recovery of species was carried out by West Bali National Park (WBNP) through release activity and collaboration with conservation organization for release in different place from their natural habitat. The population of bali starling on both locations is tend to decrease, the study aimed to analized the impact of human factor with the existence of bali starling based on geographic information system. The farthest point of bali starling existence form road distance is 1 359 meters on WBNP and 660 meters on Nusa Penida Island, while the closest point on both locations is 0 meter from road distance. The second human factor is village distance with the farthest point of bali starling is 7 296 meters on WBNP and 295 meters on Nusa Penida Island, while the closest point of bali starling is 543 meters on WBNP and 0 meter on Nusa Penida Island. The third human factor is community’s garden distance with the farthest point of bali starling is 5 696 meters on WBNP and 67 meters on Nusa Penida Island, while the closest point of bali starling is 408 meters on WBNP and 0 meter on Nusa Penida Island. The existence point of bali starling that are close to human activites have a negative impact. Bali starling will depend on the resources provided by the community on Nusa Penida Island and part of WBNP and also make it difficult for the bali starling to restore the wild nature for adaptation in natural habitat. Key words: bali starling, geographic information system, human factor, Nusa Penida, West Bali National Park